Association between vitamin D status and risk of metabolic syndrome among Korean postmenopausal women. - Seung Joo Chon (Public Library of Science (PLoS), 2014)
This study aimed to investigate the association between serum levels of 25-hydroxyvitamin D [25(OH)D] and metabolic syndrome along with its associated risk factors in Korean postmenopausal women. This study was performed using data from the KNHANES 2008-2010 study and included 4,364 postmenopausal Korean women. Clinical and other objective characteristics, seasonality, and presence of metabolic syndrome with its five components were evaluated and correlated with the serum levels of 25(OH)D. Although no statistically significant associations were observed between the levels of serum 25(OH)D and the prevalence of metabolic syndrome, the adjusted OR for elevated blood pressure, elevated triglycerides (TGs), and reduced high-density lipoprotein cholesterol (HDL-C) showed tendency to decrease sequentially as tertiles of serum 25(OH)D levels increased (p for trends  = 0.066, 0.043, and 0.010, respectively). Women in the highest tertile of serum 25(OH)D showed a significant decrease in the prevalence of elevated blood pressure, elevated TGs, and reduced HDL-C as compared with those in the lowest tertile of serum 25(OH)D (p = 0.020, 0.014, and 0.002, respectively). Based on these results, we consider that adequate serum levels of 25(OH)D in Korean postmenopausal women may not entirely indicate a lower risk of developing metabolic syndrome. However, adequate serum levels of 25(OH)D are significantly associated with a decrease in elevated blood pressure, elevated TGs, and reduced HDL-C levels in postmenopausal women.